2009
DOI: 10.1155/2010/487197
|View full text |Cite
|
Sign up to set email alerts
|

Stability Indicating RP‐HPLC Method for Determination of Valsartan in Pure and Pharmaceutical Formulation

Abstract: A simple, rapid and accurate and stability indicating RP-HPLC method was developed for the determination of valsartan in pure and tablet forms. The method showed a linear response for concentrations in the range of 50-175 µg/mL using 0.01 M NH4H2PO4(pH 3.5) buffer: methanol [50:50] as the mobile phase with detection at 210 nm and a flow rate of 1 mL/min and retention time 11.041 min. The method was statistically validated for accuracy, precision, linearity, ruggedness, robustness, forced degradation, solution … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 6 publications
0
8
0
Order By: Relevance
“…Some methods have been published for simultaneous determination of studied ARA-II-drugs including Spectrophotometry [7], HPLC-DAD [2], HPLC with fluorimetric detection [1] and capillary zone electrophoresis [8,9]. Some stability studies were reported for Losartan [10][11][12][13], Irbesartan [14,15], Valsartan [16][17][18] and Telmisartan [19]. But no published method depends on optimum stress test conditions [20] and it is the first stability study which comprises the four ARA-II compounds together.…”
Section: Introductionmentioning
confidence: 99%
“…Some methods have been published for simultaneous determination of studied ARA-II-drugs including Spectrophotometry [7], HPLC-DAD [2], HPLC with fluorimetric detection [1] and capillary zone electrophoresis [8,9]. Some stability studies were reported for Losartan [10][11][12][13], Irbesartan [14,15], Valsartan [16][17][18] and Telmisartan [19]. But no published method depends on optimum stress test conditions [20] and it is the first stability study which comprises the four ARA-II compounds together.…”
Section: Introductionmentioning
confidence: 99%
“…The pH value in all VAL syrups was not changed significantly during the study period at either temperature. Degradation of VAL in strongly acidic solutions is much faster than under alkaline conditions (23,24), but less acidic solutions do not cause degradation, as can be concluded from the good stability of VAL in Ora ® syrups (pH 4-5) (7,25,26).…”
Section: Valsartanmentioning
confidence: 91%
“…Ultra‐performance liquid chromatography (UPLC) using 1.7 μm particles and a suitable system provides a significantly greater resolution while reducing run times and improving sensitivity during the determination of many compounds. Currently, the vast majority of drug determination, including sartans, is performed by applying HPLC with conventional UV detectors (Tables ) . Their widespread application arises from the possibility of separating analyzed compounds from a mixture of other ingredients in the pharmaceutical preparation [e.g., HCT, ramipril (RAM), ENA, AML, nebivolol hydrochloride (NEB), captopril (CAP), and amiloride (AMD)], in the presence of impurities, including degradation products.…”
Section: Methodology For Determining Sartans In Raw Materials Pharmamentioning
confidence: 99%